The Description Of Allergic Contact Dermatitis At Gotong Royong I Primary Clinic Surabaya - Purworizky, Dinar A; Harijati, Erna; Kartikawati, Lucia R (JOURNAL OF WIDYA MEDIKA JUNIOR, 2019)
Introduction : Allergies are one of the immune reaction caused by a substance called an allergen. One way an allergen may affect allergy sufferers is by direct contact. If after contact with an allergen sufferers experience changes in the skin, then those change is called allergic contact dermatitis. Aim: To describe the allergic contact dermatitis at Gotong Royong I Primary Clinic Surabaya. Methods : This study is a descriptive study. Data collected by recording the variables such as age, gender, source of allergens, pattern morphology, and the predilection area on data collector sheet based on the results of an examination by a doctor to patients with allergic contact dermatitis at Gotong Royong I Primary Clinic Surabaya in the period from June 13, 2016 until August 31, 2016. The sampling method is using total sampling technique. Result : This study showed on 53 patients. The highest age group was on a Toddlers group (0-5 years old) with 29 patients (54.7%). Women suffered allergic contact dermatitis more than men, as many as 30 patients (56.6%). Source of allergens mostly caused by cosmetics, as many as 15 patients (28.3%). Morphological pattern was mostly acute pattern, as many as 33 patients (62.3%). Predilection areas were located mainly in the area of the upper extremities, as many as 15 patients (28.3%). Conclusion : This study shows that more female subjects were diagnosed with allergic contact dermatitis by doctors. Allergic contact dermatitis in the subjects of the study was mostly caused by cosmetics